(untitled) (Journal of Surgical Sciences, 2019)
Background: Evaluation of the safety and efficacy of day case laparoscopic cholecystectomy in a teaching hospital may influence the rationale of this practice to gain widespread acceptance. Methods: Day case laparoscopic cholecystectomy was offered to patients during a two and a half year period (Jan 2010 - July 2012) in Minimally Invasive Surgery unit in BSMMU who met the following established inclusion criteria: ASA (American Society of Anesthesiology) physical status classification classes I and II; age: 18 - 70 years; body mass index (BMI) < 30 kg/m2; patient acceptance and cooperation (informed consent). Acute cholecystitis was considered as an exclusion criterion. Follow-up was done by clinical examination on an outpatient basis one week and 3 months after operation. Evaluation was done about success rates, postoperative outcome (complications, readmissions, morbidity and mortality) and patient’s overall satisfaction. Results: 40 consecutive patients, predominantly female (62.5%) and ASA II (75%) with a mean age 44 ± 13.3 years underwent cholycystectomy. 85% patients had symptomatic gallstone disease. Mean operating time was 45±15.1 minutes and no conversion was needed. 25% cases experienced post operative nausea and vomiting and all patients were discharged in the following morning. 20% developed minor complications that resolved spontaneously. 1 case was readmitted and overall patient satisfaction rate was 90%. Conclusions: This study suggested that day case laparoscopic cholecystectomy is clinically effective and can be performed safely in a teaching hospital by competent surgeon. Journal of Surgical Sciences (2014) Vol. 18 (1) : 15-19